Accelerated shelf life estimation of pumpkin bar using arrhenius-based aslt with aluminum foil packaging - roziana roziana; Lily Restusari; Yessi Alza; Gusnedi Gusnedi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Pumpkin bars are practical functional food products; however, their distribution is often hampered by a lack of data on quality degradation kinetics in the tripos environment. This study aimed to estimate the shelf life of pumpkin bars using the Accelerated Shelf Life Test (ASLT) method with the Arrhenius approach and to evaluate the effectiveness of aluminum foil packaging in maintaining product quality. This study used an experimental design conducted at the Food Laboratory of the Riau Ministry of Health Polytechnic and SIG Laboratory from January to October 2025. Samples were stored at 35, 40, and 45°C, and a control temperature of 18°C for 30 days, with observations every 7 days. The parameters observed included moisture content, water activity (Aw), and the presence of mold and yeast. Data analysis used the Arrhenius kinetic model to calculate the reaction rate constant and estimate the shelf life. The results showed that the product was stable in terms of mold and yeast <10 colonies/g. Increased moisture content (8.5–14%) and Aw (0.52–0.67) were the main limiting factors for the growth of these Based on Arrhenius calculations, the shelf life of the product was estimated to be 23–35 days at 35–45°C. Moisture content and sensory degradation were the main determinants of the shelf life of pumpkin bars in aluminum foil packaging.